Chrześcijańska przeszłość dla kultury integrującej się Europy - Gryżenia SDB, ks. Kazimierz (Annales. Etyka w Życiu Gospodarczym, 2008)
The last few years are the time of the ongoing integration of Europe and its vivid discussion aboutit. The thorny issue is the role and the place of Christianity in the life of Europe. Pope John Paul II hadauthoritatively taught on the issue. His teaching is a kind of antidote against those who are in favour ofEurope without God.The European culture is not a monolith since it is inhabited by many nations with a differentcharacteristic but all are rooted in the same values of the Good News acknowledged on the Continent.The present time – and especially the centuries after the Enlightenment – seems to be the time ofabandoning Christianity. As the result of such a process, Europe witnessed two totalitarian systemsresponsible for numerous crimes. A human being wanted – without God’s participation - to decideabout right and wrong. They were tempted like the first parents in Eden. They were changed from godlikehumans to objectified ones – from “homo sapiens to homo demens”.John Paul II and many authors dealing with the processes of mankind underlined the need to buildunity in Europe in close connection to Christianity. Christianity is an important element of culture inwhich the man is not restricted to his mortal life but opens up for a supernatural perspective. ThroughChristianity the European culture is richer and the man fully developed. Taking Christianity intoconsideration in his life, man can discover the truth about himself and his true relation to God.Only the truth allows man to grow and achieve his perfection, whereas falseness condemns him tothe degeneration.